A Review of the Provision of Social and Emotional Learning in Australia, the United States, Poland, and Portugal. (4th September 2017) - Bowles, Terence; Jimerson, Shane; Haddock, Aaron; Nolan, Julene; Jablonski, Slawomir; Czub, Magdalena; Coelho, Vítor
Abstract : The aim of this research is to gather preliminary information from a range of countries to develop an international perspective on Social and Emotional Learning (SEL). Currently, there is no cohesive international statement on the minimum requirements to provide SEL in schools. By bringing together a range of international perspectives it is intended that clarity will be provided from which new approaches and initiatives can be developed and researched. International researchers familiar with SEL programs in their country were asked to answer five questions about the context and processes used to teach SEL in specific countries to begin an understanding and synthesis of best practice. These questions relate to: (1) sociocultural contexts of school systems, (2) the range of SEL programs presented in each country and what is common about these programs, (3) the effectiveness of prominent SEL programs, (4) the facilitators and barriers that exist to effectively present SEL programs within the country, and (5) recommendations for the future of SEL programs. A synthesis is followed by a discussion of the future of SEL and how the SEL Interest Group may make a contribution to the current state of the literature, curriculum, pedagogy, and research that informs SEL in schools.